The Transformation of Generation Z's Character through Islamic Education in the Digital Era - Lovita Fatihah Fijrin; Nabilah Nur Zamzamy; Maharani Najwa Salsabilla (Journal of Social Studies Education and Humanities Research, 2024)
Islamic education plays a crucial role in shaping the character of the younger generation. Islamic teachings guide and support Generation Z in character development based on the principles of the Qur'an. This study aims to identify the role of Islamic education in shaping the character of Generation Z in the digital era and to analyze effective methods and strategies used in Islamic education to strengthen their character. The research employs a descriptive qualitative method to explore these dynamics. Technological advancements provide Generation Z with greater access to Islamic education through social media and online platforms, making learning more engaging and motivating. This access enables them to internalize Islamic values while navigating the challenges of the digital era. The findings of this study highlight the importance of integrating traditional and modern educational approaches to ensure that Islamic education remains relevant and impactful for Generation Z. By utilizing digital tools effectively, Islamic education can instill strong moral values and resilience in the younger generation, preparing them to face the complexities of modern life without compromising their faith and identity